Optimal feedbacks in techno-economic dynamics. (1st January 2002) - Tarasyev, Alexander M.; Watanabe, C.; Zhu, B.
The objective of this work is twofold: to design control strategies which optimise production, technology and their rates in a nonlinear model of economic growth; and to demonstrate the significance of this modelling approach by means of an empirical analysis. We formulate a problem of optimal R&D investment for a dynamic model, which binds production to technology. A discounted utility function, which correlates the amount of sales with the diversity in production, gives a criterion of optimality. We use the Pontryagin maximum principle for the design of an optimal nonlinear dynamics. On the basis of the theoretical analysis, we carry out an empirical analysis, which attempts to demonstrate the practical significance of the approach. For Japan's major manufacturing sectors, we compare optimal and actual levels of R&D intensities and identify sources of "pseudo innovation" in high-tech industries